Sharia Methods for Developing the Talent of Reason in Children and Boys - Hussein Sari Khader, (Islamic Sciences Journal, 2025)
The research aims to extrapolate the legitimate methods in developing the child’s mind and apply them to his reality, so that he becomes able to think and face the problems and challenges of contemporary life in the way that the Glorious Quran, the Prophet’s Sunnah, and the righteous predecessors of the nation and its scholars have drawn up, which is the safe station for creating a conscious generation. This research includes a quick look at the meaning of the subject’s vocabulary, then the role of the family in developing the child’s mind, followed by talking about reviving the observation of Almighty Allah in the souls of children, and ends by talking about teaching children the Glorious Quran and the Prophet’s biography and their impact on developing the mind.